PELATIHAN DIGITAL MARKETING BAGI PENGRAJIN CETAKAN KUE DI DESA CANDI KABUPATEN SIDOARJO - Zulifah Chikmawati; Atik Widiyanti; Catur Lega Wibisono (Universitas Nahdlatul Ulama Sidoarjo, 2020)
A small business is a business that is included in the small industrial sector, whether carried out by individuals or households by utilizing goods to be processed to become goods that are more useful and valuable. Based on the analysis of the situation and problems that occurred in the cake mold craftsmen business group in Candi Village, Sidoarjo Regency, the framework for solving the problem is to use a training and mentoring approach method. Therefore, training related to digital marketing for a group of cookie cutter craftsmen in Candi Village, Sidoarjo Regency. The conclusion of this activity is that all members of the cake mold craftsmen business group in Candi Village, Sidoarjo Regency are of productive age, 87% of respondents can understand online marketing materials, only 13% or 4 respondents cannot understand online marketing materials, and 93% of respondents have diversify pastry mold products.